Hubungan Dukungan Keluarga Terhadap Self-management Lansia Dengan Penyakit Tidak Menular di Posyandu Lansia/ Family Support Relation to Self-management of Elderly with Non-communicable Diseases - Ferdinandus Sampe; Siti Rochani; Garbito Pamboaji (YCMM, 2024)
Non-communicable diseases are diseases whose incidence continues to increase with age. The aim of this research is to find out whether there is a relationship between family support for elderly self-management and non-communicable diseases (NCDs) at the PKM Rangkasbitung Banten Elderly Posyandu. This research used a cross sectional design with a sampling number of 71 respondents, sampling using a total sampling technique. The results obtained were that the majority of respondents were women 41 (57.7%) and the ages of the respondents were mostly young elderly (60-69 years), namely 40 (56.3%) and the majority of respondents suffered from hypertension 51 (71.8%). Of the 42 (59.2%) respondents who received high support, 39 (92.9%) had high self-management and 3 (7.1%%) respondents who received low family support. The results of the chi square analysis obtained a p value of 0.000 (p<0.05) with an odds ratio value of 18.42, this shows that there is a significant relationship between family support and self-management of the elderly and PTM at PKM Rangkasbitung Banten. It is expected that health workers and their families can provide support and motivation to the elderly to improve their health status, especially in improving self-management of the PTD disease they suffer from.